Effect of Calisthenic exercise on stress response among School going children in selected school of Bhubaneswar, Odisha - Sahoo, Smrutirekha; V. J, Dhanya; Shee, Kalpana; Lenka, Durgesh Nandini; Pradhan, Jayashree; Behera, Subhasmita (Journal of Neonatal Surgery, 2025)
Introduction: Calisthenic exercises helps the body become firmer and more energized, which improves general health and promotes mental health, which has found helpful in reducing stress, and anxiety. Aim of the study: The purpose of this study was to assess the effectiveness of Calisthenic exercises on stress among school going children. Method: Randomized controlled study, 220 school-age youngsters, were randomly allocated into two equal groups: the experimental group (n = 110) and the control group (n = 110) were assigned by Callisthenic exercises for 30 minutes each day for three weeks. Each participant received a self-structured questionnaire to collect demographic data. Perceived Stress Scale collected measures of degree of stress - Children (PSS - C). Result: After completed Calisthenic exercises, 57.27% of children had moderate stress level. Experimental group participants recorded better stress level reduction than the control group. The level of stress ratings before and after the test were significantly different (U value=3198, p value=0.00001) with mean difference 20.98, SD was +5.82 at 0.05 level of significance. Conclusion: Calisthenics are a type of exercise that both lowers mental tension and physically promotes brain function. Additionally, making Calisthenics a regular part of the education curriculum in schools may assist in improving children' cognitive and psychological wellness